Epidemiology and clinical aspects of hematological malignancies at the military hospital of Antananarivo - Refeno, Valéry; Hasiniatsy, Nomeharisoa R. E.; Ramahandrisoa, Andriatsioharana V. N.; Rakoto, Fanomezantsoa A.; Rakoto Alson, Aimée O.; Rafaramino, Florine (International Journal of Research in Medical Sciences, 2019)
Background: Malignant hemopathies constitute a group of pathologies having in common the anomalies of the bone marrow or of the lymphatic system cells. In developed countries, the number and actual distribution of cancers is provided by cancer registries. In Madagascar there is no effective cancer registry and only two studies on malignant hemopathies have been carried out to date, but neither has described their epidemiology and clinical aspects. Thus, we aimed to describe the epidemiology and clinical aspects of malignant hemopathies managed in the Medical Oncology Unit of the Military Hospital of Antananarivo. Methods: It was a cross-sectional and descriptive study carried out at this unit from 1st December 2012 to 31st August 2015 (33 months). Authors included all patients followed, then excluded those without pathologic evidence, cases of monoclonal gammapathy of unknown significance and cases of solid cancers. Results: We followed up 57 cases of malignant hemopathies. The mean age was 49.39±15.46 years and the sex ratio was 1.71. Superficial lymphadenopathy was the most frequent warning signs (31.58%) and lymphomas were most represented (52.63%). There was a significant association between warning signs and diagnosis (p value <0.001). Conclusions: Present results are grossly similar to those of other African authors. Present results are distinguished by a low proportion of chronic myeloid leukemia and a very low proportion of chronic lymphocytic leukemia compared to literature data. The effectiveness of the cancer registry will allow us to improve the knowledge about frequency and current distribution of cancer in Madagascar.